PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN VIDEO ANIMASI TERHADAP PEMAHAMAN KONSEP SAINS SISWA SEKOLAH DASAR - Nita Melia; Fitri Nuraeni; Nenden Permas Hikmatunisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
One of the most important abilities that students need to have is the ability to comprehend scientific ideas.  “TIMSS results and a number of research, however, show that scientific idea understanding in Indonesia is still low.  Using a video-assisted Contextual Teaching and Learning (CTL) method in the classroom is one technique to deal with this problem.  The purpose of this study is to ascertain how much elementary school students' comprehension of scientific topics is improved and affected when they use animated movies in conjunction with the Contextual Teaching and Learning (CTL) approach”.  This study employs the quasi-experimental method and is quantitative in nature.  The participants in this study were all fourth-grade elementary school children at SDN Karang Setia 01, with 26 kids in the experimental class and 26 students in the control class.  Purposive sampling was used for the sample process.  A science concept knowledge test and non-test tools in the form of student activities during the learning process were the instruments employed in this study.  According to the study's findings, students who used the CTL technique with the help of N-Gain animated movies had a 0.30 increase in concept understanding, and the CTL strategy with the help of animated videos had a 30.9% impact on students' comprehension of science concepts.  These findings suggest that the CTL method, with the use of animated movies, can be used to enhance elementary school pupils' comprehension of scientific concepts.